Analisis Kemampuan Pemahaman Konsep Matematis Siswa Kelas VIII B SMP Kristen Karuni pada Materi Peluang - Wara, Destriyati Saputri Lende; Making, Samuel Rex Mulyadi; Lubur, Dorothea Novia Ludo; Lede, Yulius Keremata (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study aiams to analyze the mathematical concept comprhension capabilities of eight grade students of Karuni Christian Junior High School on the topic of probability. Comprehenson of mathematical concept is a fundamental aspect of matheatics learning that enables students to understand mathematical ideas in depth and apply them in various situations. The topic of probability was chosen because it is considered of the difficult topic by students and requires a strong conceptual understanding. This reaseacrh uses qualitative descritive research methods with a qualitative approach. The reasearch subjects are 26 students of class VIII B of Karuni Christian Junior high school for the 2024/2025 academic year. Data colletion techniques include written tets, interviews, and documenation. The research instruments consist of test questions and interview guidelines developed based on indicators of mathematical concept understanding according to Kilpatrick, Swafford, and Findell. The research result show that students abllity to understand mathematical concepts in the material of probability is in the high category with a percentage 80%, students with a medium abillity are at 75%, and students with low abillity are at 50%. The indicator most masterred by students in the abillity to restate concepts, while the most difficult indicator is presenting concepts in the form of representations.